Revealing the Social Criticism in Literary Works: An Objective Study of Laskar Pelangi and The Grapes of Wrath - Ganap, Nindy N.; Luntungan, Grace S.; Mamentu, Agustine C. (English Education Department, 2025)
This article examines the social criticism expressed in two literary works: Laskar Pelangi by Andrea Hirata and The Grapes of Wrath by John Steinbeck. Using a descriptive qualitative method and an objective approach, the study focuses on analyzing intrinsic elements such as themes, characters, and conflicts within the texts. Laskar Pelangi portrays the social realities in Belitung, Indonesia, highlighting issues such as social inequality and limited access to education while delivering a message of hope and perseverance through the struggles of underprivileged children. In contrast, The Grapes of Wrath captures the hardships faced by migrant farmworker families in the United States during the Great Depression, emphasizing labor exploitation and the importance of social unity. Although the two works emerge from different cultural and historical backgrounds, they converge on the themes of social injustice and the pursuit of societal transformation. The findings demonstrate that literature serves as a powerful medium for articulating social critique and fostering awareness of significant societal issues. This analysis reinforces the role of literary works in illuminating social realities and inspiring critical reflection among readers. The research employs an objective study method to ensure an impartial evaluation of the texts' intrinsic elements.